PENILAIAN KINERJA PERUSAHAAN MELALUI PENERAPAN KONSEP BALANCED SCORECARD - Mayla Surveyandini; Ady Achadi (Majalah Imiah Manajemen & Bisnis, 2020)
The study with the title "Corporate Performance Assessment Through the Application of the Balanced Scorecard Concept" aims to assess company performance through the concept of balanced scorecard, which includes all four perspectives which are viewed from a financial perspective, consumer / customer perspective, internal business process perspective and learning and growth perspective. The results of this study are expected to make a positive contribution to both the company and other parties. The samples used are employees and teaching staff in the American English Course environment and the sampling technique uses simple random sampling method. Assessment from a financial perspective uses 3 (three) ratios, i.e. liquidity ratios consisting of current ratio and quick ratio. The solvency ratio consists of debt ratio and debt to equity ratio and profitability ratio consists of return on assets and return on equity. For the consumer / customer perspective using the customer profitability ratio. Internal business perspective uses the ratio of administrative expense to total revenue. While the growth and learning perspective uses benchmarks for employee productivity, employee training and employee satisfaction. For employee satisfaction variables using data validity and reliability testing, where the results indicate the instrument items are valid and reliable statements